Sphingosine-1-Phosphate Catabolizing Enzymes Predict Better Prognosis in Triple-Negative Breast Cancer Patients and Correlates With Tumor-Infiltrating Immune Cells - Nema, Rajeev; Kumar, Ashok (Frontiers in Molecular Biosciences, 2021)
BACKGROUND: Triple-negative breast cancer (TNBC) is associated with a poor prognosis. Sphingosine-1-phosphate (S1P), a potent sphingolipid metabolite, has been implicated in many processes that are important for breast cancer (BC). OBJECTIVE: In this study, we have analyzed the prognostic value of S1P metabolizing genes and their correlation with tumor-infiltrating immune cells in BC patients. METHODS: Prognostic value of S1P metabolizing genes and receptors was analyzed by multiple publicly available computational tools. The association between the gene expression and infiltration of immune cells in the tumors was analyzed by ‘Tumor-Infiltrating Immune Estimation Resource.’ RESULTS: TNBC patients with lower expression of SGPP1 or PLPP3 have much shorter relapse-free survival than the patients with a higher expression of these genes. SGPP1 and PLPP3 expression show a strong positive correlation with tumor-infiltrating dendritic cells (DCs), CD4+ and CD8+ T cells, neutrophils, and macrophages in the TNBC subtypes. In addition, S1PR4, an S1P receptor exhibit a strong positive correlation with DCs, CD4+ and CD8+ T cells and neutrophils in TNBC. We, therefore, conclude that low expression of SGPP1 and PLPP3 may hinder the recruitment of immune cells to the tumor environment, resulting in the blockage of cancer cell clearance and a subsequent poor prognosis.